1994
DOI: 10.2307/3432233
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Carcinogenesis by Crystalline Silica in Relation to Oxygen Radicals

Abstract: The carcinogenic effects of crystalline silica in rat lungs were extensively demonstrated by many experimental long-term studies, showing a marked predominance for adenocarcinomas originating from alveolar type II cells and associated with areas of pulmonary fibrosis (silicosis). In contrast with its effects in rats, silica did not induce alveolar type II hyperplasia and lung tumors in mice and hamsters, pointing to a critical role for host factors. Using these animal models, we are investigating the role of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 0 publications
4
28
0
Order By: Relevance
“…It was observed that exposure of rats to high doses of silica either by intra-tracheal instillation or by inhalation can produce lung cancer [51][52][53] , suggesting that silica itself is carcinogenic in rats. However, our meta-analysis suggested that 'silicosis induced by silica', rather than 'silica itself', increases lung cancer risk in humans, which was also supported by the following evidence: 1) when Saffiotti et al observed in detail the lung tissue of rats injected with crystalline silica into the trachea, they found that adenocarcinomas of alveolar type II origin were developed near granulomas with fibrosis in the lung 54) . In their words, the tumor was 'associated with areas of pulmonary fibrosis (silicosis)'.…”
Section: Discussionsupporting
confidence: 67%
“…It was observed that exposure of rats to high doses of silica either by intra-tracheal instillation or by inhalation can produce lung cancer [51][52][53] , suggesting that silica itself is carcinogenic in rats. However, our meta-analysis suggested that 'silicosis induced by silica', rather than 'silica itself', increases lung cancer risk in humans, which was also supported by the following evidence: 1) when Saffiotti et al observed in detail the lung tissue of rats injected with crystalline silica into the trachea, they found that adenocarcinomas of alveolar type II origin were developed near granulomas with fibrosis in the lung 54) . In their words, the tumor was 'associated with areas of pulmonary fibrosis (silicosis)'.…”
Section: Discussionsupporting
confidence: 67%
“…Intrapleural administration of crystalline silica in rats leads to the induction of localized malignant histiocytic lymphomas. Epidemiological studies have also shown an increased lung cancer risk in workers occupationally exposed to silica (3,26,43). Based on evidence obtained from animal and epidemiological studies supported by limited molecular studies, the International Agency for Research on Cancer has classified crystalline silica and cristobalite in certain occupational settings as group I human carcinogens (28).…”
mentioning
confidence: 99%
“…Previous studies have shown that freshly fractured silica is capable of generating reactive oxygen species (ROS) upon reaction with aqueous media (42)(43)(44)46). These reactive species were reported to be involved in the silica-induced lipid peroxidation and membrane damage that lead to the loss of membrane integrity and eventual pulmonary injury (45,46).…”
mentioning
confidence: 99%
“…Experimental evidence of the carcinogenicity of quartz particles is based on the results of long-term inhalation and intratracheal instillation studies of rats, which are summarized in Tables 22 and 23 [Saffiotti et al 1996]. Several issues are apparent from the results of the rat studies [Holland 1995]: 1.…”
Section: Carcinogenicitymentioning
confidence: 99%
“…Although new long-term carcinogenesis studies in animals may provide information about dose-response relationships and inhibition of quartz toxicity or reactivity in vivo, in vitro studies are needed to develop effective cellular and molecular models of carcinogenesis [Holland 1995;Saffiotti et al 1996].…”
Section: Carcinogenicitymentioning
confidence: 99%